A comparative study between the efficacy of tranexamic acid and ibuprofen for treatment of menorrhagia induced by copper T-380A intrauterine device - Mohamed Saad Shahin; Abdullah Khalil Ahmed; Samir Khamis Galal (Wolters Kluwer Medknow Publications, 2021)
Background Menorrhagia is menstrual blood loss, which interferes with a woman's physical, emotional, social, and material quality of life, and which can occur alone or in combination with other symptoms. Ibuprofen is one of the most common NSAIDs used for treatment of heavy menstrual bleeding. Tranexamic acid is the best option for those who experience irregular uterine bleeding and plan to become pregnant in the near future. Objective To evaluate and compare the efficacy of tranexamic acid and ibuprofen in controlling menorrhagia induced by copper T-380A intrauterine device (IUD). Patients and methods This prospective randomized comparative parallel study between tranexamic acid and ibuprofen for treating copper-IUD-induced menorrhagia included 100 women who attend outpatient clinic at Al-Hussein University Hospital from October 2019 to March 2020. Results Mean menstrual days in both group 1 and group 2 decreased significantly from the first month after IUD insertion to 6 months after treatment. Conclusion Tranexamic acid as an antifibrinolytic agent and Ibuprofen as an NSAID, at a dosage of 500 mg capsules of tranexamic acid three times a day and 400-mg tablet of ibuprofen three times a day orally, have the same significant effects on copper T-380A IUD-induced menorrhagia. Their effects are on both the volume of blood loss and the duration of menses.